Peran Kesetaraan Gender Terhadap Upaya Peningkatan Kualitas Hunian Dan Kualitas Hidup Dalam Program Bantuan Stimulan Perumahan Swadaya (BSPS) - Kholifah, Ananda Nur; Marseto, Marseto; Oktafia, Renny (Equalita: Jurnal Studi Gender dan Anak, 2023)
This study aims to examine the role of gender mainstreaming in efforts to improve the quality of housing and quality of life with the Self-Help Housing Assistance Program (BSPS). This analysis uses qualitative research methods of observation, interviews, literature studies, and documentation in Jombok Village, Pule District, and Trenggalek Regency. Efforts to improve the quality of housing and quality of life were validated by looking at the condition of the house before and after the BSPS program's assistance. From the results of the study, it was found that the role of gender mainstreaming in improving the quality of housing and living standards was running quite well and was able to achieve success. The implementation of the Self-Help Housing Assistance Program (BSPS) has successfully implemented aspects of gender equality, including Access, benefits, control, and participation. The fulfillment of these four aspects is a sign of the successful implementation of gender mainstreaming in BSPS operations in Trenggalek Regency.